Using IFP To Improve Reading And Writing Skills In Lower Grades - Muhammad Fikri Nurzaman; Dyah Lyesmaya; Utomo (Lembaga Bale Literasi, 2026)
This study aims to evaluate the effectiveness of integrating an Interactive Flat Panel (IFP) with Wordwall interactive media to improve early reading and writing skills in lower elementary grades. Employing a quantitative approach with a quasi-experimental one-group pretest-posttest design, this research examined a total population of 22 first-grade students using exhaustive sampling. Data were gathered through structured cognitive written tests and observation sheets tracking student-multimedia interactions. Due to non-normally distributed data verified via the Shapiro-Wilk test, the quantitative data were analyzed using descriptive statistics, Normalized Gain (N-Gain), and the non-parametric Wilcoxon signed-rank test via SPSS software. The results showed a significant increase in literacy performance, where the mean score rose from 75.91 at pretest to 88.18 at posttest 1, supported by a Wilcoxon p-value of 0.000 and a moderate N-Gain score of 0.5455. Furthermore, a delayed posttest 2 revealed strong retention effect consistency, with scores stably increasing to 90.91 after a time interval. In conclusion, the structured integration of IFP and Wordwall effectively accelerates and sustains long-term foundational literacy skills among lower-grade students.